Influence of Personal Traits, School Environment, and Social Environment on Teachers' Work Stress in Honghe Vocational and Technical College - Bai, Xutong; Putachote, Nitipon (Prosiding University Research Colloquium, 2025)
This study takes teachers in vocational and technical schools as the research object, and discusses the influence of general demographic data, personal traits, school environment, and social environment on work stress. This paper uses quantitative research methods and various statistical methods, including descriptive analysis, correlation analysis, and regression analysis, to investigate the relationship among demographic variables, personal traits, school environment, social environment, and work stress. Finally, based on these findings, some suggestions are put forward. The results of this study provide theoretical support for vocational and technical schools to help teachers formulate effective strategies to manage work stress in the current employment environment. By paying attention to key factors such as demographic variables, personal traits, school environment, and social environment, this research offers a theoretical basis for alleviating work stress and improving the well-being of vocational and technical school teachers.